2008
DOI: 10.1177/0273475307312197
|View full text |Cite
|
Sign up to set email alerts
|

The Role the Collegiate American Marketing Association Plays in Professional and Entrepreneurial Skill Development

Abstract: Professional student organizations offer members a wide range of learning opportunities for applied marketing experiences. Little research exists in the marketing education literature on the role student organizations play in preparing their members for life beyond school. Understanding what students seek as members of such organizations and how satisfied they are with their experiences is not only important for continued chapter development but also useful for faculty not directly involved with such organizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…The overall response rate regardless of open rate was 21.2% (1802/8500). These response rates compare favorably for a national online survey of college students (14). The profile of respondents is provided in Table 1.…”
Section: Methodsmentioning
confidence: 78%
“…The overall response rate regardless of open rate was 21.2% (1802/8500). These response rates compare favorably for a national online survey of college students (14). The profile of respondents is provided in Table 1.…”
Section: Methodsmentioning
confidence: 78%
“…For example, marketing organizations, lunch/learn sessions, speaker series, as well as campus career centers can focus on topics such as resume preparation, interview skills, professional dress, follow-up, and etiquette. Using collegiate marketing organizations as a means of improving career development skills supports, Peltier, Scovotti, and Pointer (2008) found that activities involving networking and interpersonal skills were perceived as most important by students and had a strong impact on student satisfaction. Activities having the most impact on satisfaction were those involving professional contacts (Peltier et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…These response rates compare favorably for a national online survey of college students. 30 The profile of respondents is provided in Table 1. This profile aligns with the CAMA's annual conference membership survey in terms of sex (69% female in sample, 67% female in member survey) and class standing (45% seniors sample, 47% member survey).…”
Section: Methodsmentioning
confidence: 99%